Neuro- and immunomodulatory steroids and other biochemical markers in drug-naive schizophrenia patients and the effect of treatment with atypical antipsychotics - Bicikova, Marie; Hampl, Richard; Hill, Martin; Ripova, Daniela; Mohr, Pavel; Putz, Zdenek (Neuro endocrinology letters, 2011)
OBJECTIVE: Serum levels of neuro- and immunomodulatory adrenal steroids together with selected hormonal, lipid and other relevant biochemical parameters were investigated to examine the differences between first-episode schizophrenia patients and age-matched healthy subjects, and the effect of treatment with atypical antipsychotics. METHODS: The patient´s group consisted of 22 drug-naive patients (13 men and 9 women), diagnosed with schizophrenia according to ICD-10 criteria, before and after six-months treatment with atypical antipsychotics of olanzapine or non-olanzapine type. Biochemical markers included steroids cortisol, dehydroepiandrosterone, its sulfate, 7-hydroxylated metabolites of dehydroepiandrosterone, prolactin, thyrotropin, free thyroxine, autoantibodies against thyroid peroxidase and thyroglobulin, glucose levels, four major lipid parameters, homocysteine and three other aminothiols. Steroids, prolactin and thyroid parameters were determined by radioimmunoassays, the other markers by standard biochemical methods. RESULTS: Significantly lower dehydroepiandrosterone sulfate and of 7α-hydroxy- dehydroepiandrosterone levels than in controls were found in male patients. In the female group, the only difference in steroid spectra was significantly higher cortisolemia in the patients. The patients had also higher titres of autoantibodies against thyroid peroxidase. Compared to controls, the patients displayed worse lipid spectra, and higher homocysteinemia. Medication did not lead to significant changes in the parameters, with the exception of expected increase in prolactin levels in non-olanzapine treated subgroups. CONCLUSION: Lower levels of 7α-hydroxydehydroepiandrosterone, abundant especially in brain, determined for the first time in schizophrenia patients, are in agreement with recent opinion of their neuroprotective and immunoprotective role. High levels of autoantibodies against thyroid peroxidase in the patients support the autoimmunity hypothesis of schizophrenia.
Keywords: jodidperoxidasa; Humans; Case-Control Studies; neurotransmiterové látky; Hydrocortisone; hydrokortison; studie případů a kontrol; homocystein; schizofrenie; Female; dospělí; Neurotransmitter Agents; výsledek terapie; lidé; Biomarkers; Iodide Peroxidase; Schizophrenia; prolaktin; Homocysteine; steroidy; Adult; Prolactin; imunologické faktory; antipsychotika; biologické markery; ženské pohlaví; Male; protilátky; Sex Characteristics; Treatment Outcome; Antibodies; Immunologic Factors; pohlavní dimorfismus; Antipsychotic Agents; mužské pohlaví; Steroids; dehydroepiandrosteron; Dehydroepiandrosterone